The Bellboy [videorecording (DVD)] - Lewis, Jerry, 1926-2017; Gerry, Alex; Clayton, Bob (Widescreen DVD collection., 2004)
Stanley is just one in the small army of unsung heroes who keep the Hotel Fontainebleau in Miami Beach operating. Or at least, that's the goal. With Stanley on board, you can be sure that anything and everything will go wrong with side-splitting results.